2011
DOI: 10.1007/s10735-011-9322-x
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of CXCR7/ligands may be involved in oral carcinogenesis

Abstract: Oral carcinogenesis is a multistep process and requires accumulation and interplay of a series of molecular events. Chemokines and their receptors have been suggested to play important roles in the initiation or progression of cancers. Until now, no report focuses on their alterations in premalignant stage of oral squamous cell carcinoma (OSCC). Compared with normal tissues, mRNA levels of 9 chemokines and 3 chemokine receptors including CXCR7 in oral leukoplakia (OLK) were increased more than two folds by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Moreover, we show that colon and gastric tumor tissue express relatively low levels of CXCR7 compared with the other tumor tissues analyzed. Importantly, we show a high incidence of CXCR7 protein expression in head and neck tumor biopsies, in line with previous studies where CXCR7 expression was detected in oral carcinoma patient material (45). Several human head and neck squamous cell carcinomas cells analyzed in our studies showed high expression of CXCR7, as detected by radioligand binding and anti-CXCR7 antibody staining (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we show that colon and gastric tumor tissue express relatively low levels of CXCR7 compared with the other tumor tissues analyzed. Importantly, we show a high incidence of CXCR7 protein expression in head and neck tumor biopsies, in line with previous studies where CXCR7 expression was detected in oral carcinoma patient material (45). Several human head and neck squamous cell carcinomas cells analyzed in our studies showed high expression of CXCR7, as detected by radioligand binding and anti-CXCR7 antibody staining (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, little is known about the genes involved and its relation to the invasive capacity and metastatic ability (Ha et al 2009;Schoop et al 2009;Xia et al 2011). Our group has been working on a genome-wide analysis and reported members of the ING family (Borkosky et al 2009;Cengiz et al 2010;Gunduz et al 2000Gunduz et al , 2002Gunduz et al , 2005 and Dickkopf (Dkk) family (Katase et al 2008(Katase et al , 2010 as candidate TSGs in head and neck SCC.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR7 was also expressed in 85% of oral leukoplakia and 86% of oral squamous cell carcinoma, whereas only 8% of normal tissues displayed CXCR7 immunostaining at the protein level. In addition, CXCR7 was concomitantly expressed with its ligands SDF-1α and I-TAC in all oral leukoplakia and oral squamous cell carcinoma tissues, suggesting that the CXCR7-SDF-1α/I-TAC axis is important in oral carcinogenesis (32). Recently, Maussang et al (33) demonstrated a high CXCR7 expression in head-and-neck cancer biopsies, highlighting a potential novel tumorigenic role of CXCR7 in these types of cancer.…”
Section: Cxcr7 In Cancer Of the Gastrointestinal Systemmentioning
confidence: 98%
“…The biological properties of squamous cell carcinoma are intimately regulated by various cytokines and growth factors. Recent studies in the field of chemokine systems as mediators of tumor development and progression have demonstrated that chemokine receptors play an important role in head and neck squamous cell carcinomas (31,32). Xia et al (32) reported that the expression of CXCR7 mRNA in oral leukoplakia, which is a premalignant lesion of oral squamous cell carcinoma, was increased by >2-fold compared with normal tissues as observed by microarray analysis.…”
Section: Cxcr7 In Cancer Of the Gastrointestinal Systemmentioning
confidence: 99%
See 1 more Smart Citation